Svāmi Vivēkānandaravara patragaḷa Kannaḍada anuvāda - Vivekananda, Swami, 1863-1902 (SAMP early 20th-century Indian books project, 1929)
Letters by a Hindu religious leader of the Ramakrishna Mission.